Geography sculpts the future, or: escaping—and falling back into—the tyranny of absolute space. Issue 2 (4th May 2021) - Mitchell, Don
ABSTRACT: This essay reviews developments in spatial theory since the 1960s to argue that any consideration of possible future worlds must begin from a fully dialectical, and fully materialist theory of space. Much critical social and cultural theory instead begins from as unexamined assumption of absolute space, which is deeply problematic theoretically and especially politically. By contrast, what is necessary is a theory capable of understanding not just that spaces are simultaneously absolute, relative, and relational, but how they are simultaneously absolute, relative, and relational. Fundamental building blocks of such a dialectical theory have been laid down by Henri Lefebvre, David Harvey, Doreen Massey, Neil Smith, and Cindi Katz (among many others), but the theory remains insufficiently materialist. A fully materialist, dialectical theory of space requires the re-introduction of landscape and its opposite, anti-landscape as the key mediating spatial forms. Without this, absolute space will continue its tyrannical reign, and the future geography sculpts one more of constraint than of possibility.